Plio-pleistocene continental hydroclimate and indian ocean sea surface temperatures at the southeast african margin - Taylor, Audrey K.; Berke, Melissa A.; Castañeda, Isla S.; Koutsodendris, Andreas; Campos, Hernan; Hall, Ian R.; Hemming, Sidney R.; LeVay, Leah J.; Sierra, Alejandra Cartagena; O'Connor, Keith (Paleoceanography and paleoclimatology, 2021)
Efforts to understand long-term Indian Ocean dynamics and land-sea linkages in southeast Africa during periods of significant global and regional climate change have been inhibited by a lack of high-resolution climate records, particularly during the Plio-Pleistocene. Here we present new biomarker and pollen records from International Ocean Discovery Program (IODP) Site U1478, located at the Upper Agulhas Confluence near the Limpopo River mouth, to establish environmental conditions at the southeast African margin between 4 and 1.8 Ma and address this spatiotemporal gap. Compound-specific hydrogen isotopes of terrestrial leaf waxes (δDwax) and TEX86, using marine archaeal lipids, document hydroclimate variability and sea surface temperature (SST), respectively, permitting an onshore-offshore climate comparison. The U1478 records establish the Limpopo catchment response to the switch in Indonesian Throughflow source waters, the mid-Pliocene Warm Period, and intensification of Northern Hemisphere glaciations at ∼2.7 Ma. Broad coherence between the δDwax and SST records supports a linkage between Indian Ocean temperatures and southeast African hydroclimate. We hypothesize that additional mechanisms including Indian Ocean cross-basin SST gradients (ΔSST) and high latitude glaciation acted as hydroclimate controls during the Plio-Pleistocene. We use ΔSST to evaluate ocean-atmosphere patterns similar to the Indian Ocean Dipole (IOD) and establish generally wetter conditions in the region associated with positive IOD-like phases. Additionally, an obliquity signal evident in the δDwax record indicates that glacial-interglacial variability likely influenced the tropical rain belt position and also controlled rainfall. Hydroclimate and environmental conditions across the Plio-Pleistocene in southeast Africa may have important implications for regional hominin evolution.
Gesehen am 18.05.2021